City Diplomacy Toward the Attainment of UN SDGs: Quezon City, Philippines (2019-2023) - P. Agustin, Ma. Regina (Journal of Paradiplomacy and City Networks, 2024)
Since 2019, Quezon City (QC) has actively sought to address sustainability partly through international activities. Meanwhile, the Philippines has been stagnating in the achievement of the UN SDGs. By contextualizing Kuznetsov’s (2015) paradiplomacy framework using a review of digital archival data from official government websites and reputable news outlets, this study argues that QC pursued international activities related to the UN SDGs with the help of an encouraging international and regional environment that provided opportunities for cities to participate in sustainability efforts, supportive national development directives and legal frameworks, and Mayor Belmonte’s dedication to sustainability. Furthermore, QC facilitated international activities through the creation of departments on climate change and sustainable development. These aided in Paradiplomacy activities on sustainability, which include (1) membership in international city networks, (2) participation in campaigns or commitments towards the achievement of goals related to sustainability, (3) participation in international fora and knowledge-sharing on the issue area, (4) city-to-city cooperation, and (5) partnerships with other organizations. In response, the national government has reaffirmed the role of local government units in the achievement of global goals in the realm of the environment and sustainability.